A Two-Phase Heuristic Algorithm for the Problem of Scheduling and Vehicle Routing for Delivery of Medication to Patients. (11th December 2018) - Linfati, Rodrigo; Escobar, John Willmer; Escalona, Juan
Abstract : In this paper, a two-phase hybrid algorithm to address the problem of scheduling visits to customers and the vehicle routing problem of medication delivery to highly dependent patients is proposed. In the first phase, the issue of daily scheduling for a cluster of customers is solved via a flexible mathematical optimization model applied to different scenarios. The solution obtained in the first phase generates n clusters of patients and a frequency routing problem that considers delivery periodicity, location, demand, service times, travel times, and daily load-balancing constraints. In the second phase, a hybrid metaheuristic approach including the synergy and constant iteration between simulated annealing and a record-to-record algorithm is applied to improve the initial solution obtained in the first phase. The effectiveness of the proposed algorithm is validated with real data obtained from a pilot project in Chile. The results are promising and demonstrate the efficiency of the proposed methodology.